Fatayat Nahdlatul Ulama Communication Strategy in Minimizing Prostitution Kluwih Village Branch, Bandar District, Batang Regency - Faiqotus Sakinah; Muhammad Rikzam Kamal (IQTIDA : Journal of Da'wah and Communication, 2022)
This study aims to describe the communication strategy of fatayat nahdlatul ulama in minimizing prostitution on the branches of Kluwih village, Bandar sub-district, Batang district. Prostitution is an uncontrolled behavior that is fatal for those who do it. The main factors behind the occurrence of prostitution are economic, environmental and broken home factors. This has become a public controversy, in addition to environmental economic problems that also affect the occurrence of prostitution so that the fatayat of Nahdlatul Ulama wants to minimize prostitution. This communication strategy is the communication strategy used, namely from Anwar Arifin's communication strategy who knows an audience who will receive a message so that the audience understands a message that is conveyed, the next step is to compose a message so that the message to be conveyed does not deviate from the theme and the last one uses a method so that the event which will run smoothly. Furthermore, Fatayat uses the Word Of Mouth strategy to attract an audience to take part in the event to be held by finding an audience to attend the event by using information from friends to friends, luring the community by participating in the event to get a facility, and then giving ideas to develop career. By using this strategy, the community is enthusiastic about participating in events that have been organized by fatayat nahdlatul ulama.